2007
DOI: 10.1080/00071660601156479
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of cage height and stocking density on the behaviour of laying hens in furnished cages

Abstract: 1. Limited information is available on how changes in horizontal and vertical space within enriched or furnished layer cages (as defined by Directive 1999/74/EC) influence hen behaviour. This study evaluated the effects of varying minimum cage heights and space allowances on the behaviour of laying hens housed in furnished cages. It was conducted on two flocks of medium brown hybrid hens housed in furnished cages with access to perches and nest boxes on a semi-commercial scale at ADAS Gleadthorpe. 2. Flock 1 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 20 publications
4
23
0
Order By: Relevance
“…Similarly, bird activity tends to increase with increasing group size when associated with the cage area (Carey et al, 1995;Albentosa et al, 2007), which can be explained by the synchronous feeding of hens (Hughes, 1971). In addition, Matsui et al (2004) and Elson and Croxall (2006) reported a lower feed intake for birds in furnished compared with conventional cages.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, bird activity tends to increase with increasing group size when associated with the cage area (Carey et al, 1995;Albentosa et al, 2007), which can be explained by the synchronous feeding of hens (Hughes, 1971). In addition, Matsui et al (2004) and Elson and Croxall (2006) reported a lower feed intake for birds in furnished compared with conventional cages.…”
Section: Discussionmentioning
confidence: 95%
“…In Belgium, for example, certain politicians tried to incorporate a minimum cage height of 50 cm for furnished cages but failed to do so. Although it is known that the behaviour of hens differ when housed at different cage heights (Nicol, 1987;Albentosa et al, 2007), that hens prefer taller cages (Dawkins, 1985) and seemingly are prepared to work to access a high target cage (Albentosa and Cooper, 2005), the specific link between cage height and perching behaviour has, to our knowledge, not previously been studied. The objective of this study is, therefore, to investigate the effect of cage height on perching behaviour and perch height preference in laying hens.…”
Section: Introductionmentioning
confidence: 94%
“…However, certain behaviours, notably wing flapping and flying, are rarely or never observed in cages, even at low stocking densities Albentosa and Cooper, 2004). There is some evidence from rebound studies to suggest that these behaviours are important (Nicol, 1987) but it seems that they are prevented by spatial restriction, even at allowances that exceed the current recommendation .…”
Section: Space and Social Influences On The Expression Of Behaviouralmentioning
confidence: 99%